The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.21276/aimdr.2017.3.6.sg4
|View full text |Cite
|
Sign up to set email alerts
|

Transversalis Fascia and Preperitoneal Fascia: A Laparoscopic Study of Live Surgical Anatomy during TEPP Hernioplasty – Final Report and Literature Review

Abstract: Background: Despite excellent perspective, bright lighting and high magnification afforded by preperitoneal laparoscopy, there is still little agreement among the practicing surgeons and anatomists about transversalis and preperitoneal fascias. Methods: Study Setting -Elective Clinical; Design -Prospective; Population -Adults (≥18 years); Place -J. N. Medical College Hospital, A. M. U., Aligarh; Procedure: Laparoscopic total extraperitoneal preperitoneal (TEPP) hernioplasty; Technique: Standard 3-midline-port … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
1
7
0
1
Order By: Relevance
“…[3] Fourthly, the Anatomical preperitoneal retropubic space (Space III) bounded anteriorly by the preperitoneal fascia and posteriorly by the parietal peritoneum [ Figure 1,3,5,7,9,11,13 and 15-16], corresponded to the Hayes' umbilical vesical retrofascial space. In presence of the double-layered preperitoneal fascia as reported earlier by the author, [9,11] there was found a potential space (Space IIIB) between the two layers of the double-layered preperitoneal fascia [Figure 5,7,11,13], which corresponded to the Hayes' umbilical vesical interfascial space and its upward extension, i.e., the Hayes' supravesical space [ Figure 15 and 16]. [3] In presence of a complete posterior rectus sheath as reported earlier by the author as well as by others, [6,9,[21][22][23][24][25] the complete posterior rectus sheath further divided the classical retropubic space (Space I) into two fissile potential spaces (Space IA and IB) [ Figure 9 and 11], or it might mean that the classical retropubic space was bounded posteriorly by both the complete posterior rectus sheath and the transversalis fascia, in addition to the preperitoneal fascia (single/double-layered) and the parietal peritoneum [ Figure 10 and 12].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…[3] Fourthly, the Anatomical preperitoneal retropubic space (Space III) bounded anteriorly by the preperitoneal fascia and posteriorly by the parietal peritoneum [ Figure 1,3,5,7,9,11,13 and 15-16], corresponded to the Hayes' umbilical vesical retrofascial space. In presence of the double-layered preperitoneal fascia as reported earlier by the author, [9,11] there was found a potential space (Space IIIB) between the two layers of the double-layered preperitoneal fascia [Figure 5,7,11,13], which corresponded to the Hayes' umbilical vesical interfascial space and its upward extension, i.e., the Hayes' supravesical space [ Figure 15 and 16]. [3] In presence of a complete posterior rectus sheath as reported earlier by the author as well as by others, [6,9,[21][22][23][24][25] the complete posterior rectus sheath further divided the classical retropubic space (Space I) into two fissile potential spaces (Space IA and IB) [ Figure 9 and 11], or it might mean that the classical retropubic space was bounded posteriorly by both the complete posterior rectus sheath and the transversalis fascia, in addition to the preperitoneal fascia (single/double-layered) and the parietal peritoneum [ Figure 10 and 12].…”
Section: Discussionmentioning
confidence: 54%
“…[8,11] In our study, the transversalis fascia was found invariably single-layered in all of the 68 cases of the inguinal hernia operated. However, seven combinations of twin anatomic variations of the posterior rectus sheath and preperitoneal fascia were recorded, namely, (1) single-layer incomplete posterior rectus sheath and single-layer preperitoneal fascia (64.7%); (2) double-layer incomplete posterior rectus sheath and single-layer preperitoneal fascia (2.9%); (3) single-layer incomplete posterior rectus sheath and double-layer preperitoneal fascia (4.4%); (4) double-layer incomplete posterior rectus sheath and double-layer preperitoneal fascia (7.4%); (5) single-layer complete posterior rectus sheath and single-layer preperitoneal fascia (13.2%); (6) singlelayer complete posterior rectus sheath and doublelayer preperitoneal fascia (4.4%); (7) double-layer complete posterior rectus sheath and double-layer preperitoneal fascia (1.5%) [ Table 2].…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…El espacio extraperitoneal comprende a su vez otros tantos en función de las fascias que contiene. Los trabajos de Arregi, y recientemente de Ansari, nos han mostrado los planos parietales inguinales sin distorsión 7,8 . Entre la «nueva» fascia preperitoneal y la transversalis, a nivel anterolateral, encontramos los compartimentos descritos por Retzius (retropúbico) y Bogros (retroinguinal).…”
Section: Discussionunclassified